Development of a new birthing model material based on silicone rubber/natural rubber blend - Phanutchanart Panmanee; Manunya Okhawilai; Phattarin Mora; Chanchira Jubsilp; Panagiotis Karagiannidis; Sarawut Rimdusit (Polymer Testing, 2023)
A novel material based on silicone rubber (SR) modified with natural rubber (NR) was developed. Combinations of sulfur/peroxide curing systems were used as crosslinking agents. The results showed that the incorporation of NR improved the tensile strength, tear strength and elongation at break of the SR/NR blend. It was also found that the blending of SR/NR at 90/10 provided the greatest tensile strength and elongation at break of 1.9 MPa and 1381%, respectively as well as good tear strength. The properties of this SR/NR blend and the corresponding interpenetrating polymer network (IPN) were compared and showed that the IPN provided higher tensile strength. However, the blend exhibited greater elongation at break and hardness, relatively close to human skin which are more important for a birthing model material. It can be concluded that the blending of SR/NR at 90/10 is the most promising material to substitute expensive currently used birthing model.